Metabolic perturbation of Streptomyces albulus by introducing NADP-dependent glyceraldehyde 3-phosphate dehydrogenase - Mao, Jiaqi; Zhang, Min; Dai, Wenjuan; Fu, Chenghao; Wang, Zhanzhan; Wang, Xiuwen; Yao, Qingshou; Kong, Linghui; Qin, Jiayang (Frontiers in Microbiology, 2024)
The available resources of Streptomyces represent a valuable repository of bioactive natural products that warrant exploration. S. albulus is primarily utilized in the industrial synthesis of ε-poly-L-lysine (ε-PL). In this study, the NADP-dependent glyceraldehyde 3-phosphate dehydrogenase (GapN) from Streptococcus mutans was heterologously expressed in S. albulus CICC11022, leading to elevated intracellular NADPH levels and reduced NADH and ATP concentrations. The resulting perturbation of S. albulus metabolism was comprehensively analysed using transcriptomic and metabolomic methodologies. A decrease in production of ε-PL was observed. The expression of gapN significantly impacted on 23 gene clusters responsible for the biosynthesis of secondary metabolites. A comprehensive analysis revealed a total of 21 metabolites exhibiting elevated levels both intracellularly and extracellularly in the gapN expressing strain compared to those in the control strain. These findings underscore the potential of S. albulus to generate diverse bioactive natural products, thus offering valuable insights for the utilization of known Streptomyces resources through genetic manipulation.